Адміністративно-правові засади юридичного забезпечення діяльності закладів вищої освіти зі специфічними умовами навчання : автореферат дисертації - Староста, В. І.; Starosta, V. I. (Харківський національний університет внутрішніх справ, 2023)
Дисертацію присвячено визначенню сутності та розкриттю особливостей адміністративно-правових засад юридичного забезпечення діяльності закладів вищої освіти зі специфічними умовами навчання, а також розробленню концептуальних засад, пропозицій та рекомендацій, спрямованих на вдосконалення норм чинного адміністративного законодавства у відповідній сфері. Визначаються методологічні засади юридичного забезпечення діяльності закладів вищої освіти зі специфічними умовами навчання. Надається адміністративно-правова характеристика юридичного забезпечення діяльності закладів вищої освіти зі специфічними умовами навчання. Визначаються напрямки удосконалення адміністративноправових засад юридичного забезпечення діяльності закладів вищої освіти зі специфічними умовами навчання.

The thesis is devoted to defining the essence and disclosing the peculiarities of the administrative and legal framework for legal support of higher education institutions with specific learning conditions, as well as to developing proposals and recommendations aimed at improving the provisions of current administrative legislation in the relevant area. It has been defined the methodological foundations of legal support for the activities of higher education institutions with specific learning conditions. In particular, the author has outlined the tasks and content of legal support for the activities of higher education institutions, established the essence and features of higher education institutions with specific learning conditions as an object of administrative and legal regulation, characterised the legal framework for legal support for the activities of higher education institutions with specific learning conditions and determined the place of administrative and legal provisions among them. The author has provided a general administrative and legal characteristic of legal support for the activities of higher education institutions with specific learning conditions. Namely, the author has defined the types and areas of legal support for the activities of higher education institutions with specific learning conditions, outlined the system of subjects of legal support for the activities of higher education institutions with specific learning conditions and defined the specifics of their administrative and legal status, and has summarised the administrative and legal forms and methods of legal support for the activities of higher education institutions with specific learning conditions. It has been determined the directions of improvement of administrative and legal framework for legal support of higher education institutions with specific learning conditions. In particular, the author has proposed measures to improve the administrative legislation regulating the administrative and legal framework for legal support of higher education institutions with specific learning conditions, summarised the foreign experience of legal support of higher education institutions with specific learning conditions and identified the possibilities of its use in Ukraine.

Диссертация посвящена определению сущности и раскрытию особенностей административно-правовых основ юридического обеспечения деятельности учреждений высшего образования со специфическими условиями обучения, а также разработке концептуальных основ, предложений и рекомендаций, направленных на усовершенствование норм действующего административного законодательства в соответствующей сфере. Определяются методологические основы юридического обеспечения деятельности высшего образования со специфическими условиями обучения. Предоставляется административно-правовая характеристика юридического обеспечения деятельности учреждений высшего образования со специфическими условиями обучения. Определяются направления усовершенствования административно-правовых основ юридического обеспечения деятельности учреждений высшего образования со специфическими условиями обучения.
Administrative and legal bases of legal support for the activities of higher education institutions with specific learning conditions
Keywords: Україна; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.07; заклади вищої освіти зі специфічними умовами навчання; юридичне забезпечення; адміністративно-правове регулювання; higher education institutions with specific learning conditions; administrative and legal regulation; Ukraine; legal support; заведения высшего образования со специфическими условиями обучения; юридическое обеспечение; административно-правовое регулирование; Украина